Le Nomenclator de Robert Constantin (1555), première bibliographie française ? - Magnien, Michel (Renaissance and Reformation / Renaissance et Réforme, 2011)
Even if one can discover lists of books that were printed in France before 1555, the Nomenclator seems to be the first work solely devoted to bibliographic inventory ever printed on French soil. Yet it is a relatively unknown publication – issuing from an unfamiliar hand. This thin volume, of fewer than 200 pages has not interested critics until now. Before presenting the materiality and problematic of this small in octavo, so modest when compared to the enormous in folio published by Gesner ten years earlier from which it derives, this article describes the personality and the works of R. Constantin, a preeminent Hellenist, born at Caen in 1530, and author of the Nomenclator, his first printed work. A friend of Daléchamps and a man interested in medical works, Constantin is linked to the new humanist scene. The precise analysis of the bibliographic work, title, sources, and references present in the Nomenclator show the scholarly tastes and reformed convictions of its author. This analysis also brings to light the hierarchy of bodies of knowledge and authors. Lastly, it demonstrates the ambition of its young author, namely: recognition within the humanist environment. This article concludes with a study of the reception of this first bibliography, once famous in the past.